Synthesis and Optimization of Bovine Serum Albumin Nanoparticles Immobilized with Antituberculosis Drugs - Yessentayeva, N.A.; Galiyeva, A.R.; Daribay, A.T.; Sadyrbekov, D.T.; Zhumagalieva, T.S.; Marsel, D.T. (Eurasian Journal of Chemistry, 2024)
This study involved the synthesis of bovine serum albumin (BSA) nanoparticles immobilized with the antituberculosis drugs isoniazid (INH) and rifampicin (RIF) by the desolvation method. The primary objective was to explore the impact of varying concentrations of albumin, urea, cysteine, rifampicin, and isoniazid on the average size of nanoparticles, polydispersity, and the encapsulation efficiency of drugs. The study's outcomes affirm that alterations in the concentrations of these components influence nanoparticles’ parameters, highlighting their key role in optimizing the encapsulation process and enhancing the efficacy of tuberculosis drug delivery. The nanoparticles obtaned as a result of optimization demonstrated an optimal size of 231.2±1.2 nm with a polydispersity of 0.061±0.08. Encapsulation efficiency was 89% for rifampicin and 38.5% for isoniazid. The investigation of drug release kinetics from the polymer matrix revealed a gradual release pattern. Evaluation of the obtained nanoparticles by Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) confirmed the successful incorporation of drugs into the polymer matrix. These findings highlight the potential of BSA nanoparticles as effective carriers for tuberculosis treatment, with implications for refining drug delivery strategies.
Keywords: nanoparticles; bovine serum albumin; rifampicin; isoniazid; desolvation; hydrophilic drugs; hydrophobic drugs; anti-tuberculosis drugs